Matching leadership qualities of male and female leadership from the Quranic perspective - Hilal, Huda Mohammad Hassan (IIUM Press, 2015)
The topic of female leadership has yet to be sufficiently and impartially investigated, especially from the Islamic perspective. It seems that Muslim societies do not favour appointing women as leaders of their nations, yet Muslims are in need of authentic patterns of female leadership to be imitated in the 21st century. The current study bridges the gap between original Qur’ānic teachings and dominant culture by highlighting the Qur’ānic conceptualisation of female leadership. And investigates the myth that only men are the best leaders. It identifies a set of global women who had led their societies formally or informally, as mentioned in the Qur’ān, namely Queen Āsyā, Queen Balqīs and Maryam the daughter of Imran. And matches it with the Qur’ānic male leadership derived from some parables of Prophet Muḥammad (PBUH), Dhūl-Qarniyyn, Țālūt, and Prophet Suliyymān. The research documents leader’s personality, leader-follower relation, task structure and crisis management as four principal axes to the study, relying on the dominant theories of leadership. The inference reveals conformity between both male and female patterns of leadership, except for minor differences related to physical strength, and conducting wars.